2012
DOI: 10.1007/bf03259818
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, Safety and Tolerability of Bencycloquidium Bromide, a Novel Selective Muscarinic M1/M3 Receptor Antagonist, After Single and Multiple Intranasal Doses in Healthy Chinese Subjects

Abstract: Background: Bencycloquidium bromide (BCQB) is a novel, potent and selective muscarinic M1/M3 receptor antagonist under development for the treatment of rhinorrhea in rhinitis. The pharmacokinetics and safety of BCQB in animals have been established in preclinical studies. However, no clinical pharmacokinetic data are available for BCQB in humans. Objective: The aim of this first-in-human study was to evaluate the pharmacokinetics, safety and tolerability of BCQB following single and multiple intranasal doses i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Early study on safety and tolerability of BCQB showed BCQB to be tolerable in healthy volunteers up to the dose of 480 lg, which is 2.5 fold the dosage used in the current study (Sun et al, 2012). In our study, all subjects' AUC after co-administration with paroxetine were within 1.0-1.5 fold, except for two subjects with 2 fold AUC.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Early study on safety and tolerability of BCQB showed BCQB to be tolerable in healthy volunteers up to the dose of 480 lg, which is 2.5 fold the dosage used in the current study (Sun et al, 2012). In our study, all subjects' AUC after co-administration with paroxetine were within 1.0-1.5 fold, except for two subjects with 2 fold AUC.…”
Section: Discussionmentioning
confidence: 65%
“…A series of studies have shown BCQB to be a potent drug with significant therapeutic effects on hypersensitive rhinitis, allergic rhinitis, airway-inflammation, pruritus and acute rhinitis known as common cold Xu et al, 2008;Li et al, 2011). Also, early study of BCQB in human showed its safety and tolerability after single doses escalation and multiple doses escalation (Sun et al, 2012). Our recent study showed that BCQB is metabolized mainly by CYP2D6 and also weekly by CYP3A4/5 and CYP2C19 (Agbokponto et al, 2014).…”
Section: Introductionmentioning
confidence: 96%
“…In the power model, α is the expected value of Y for a reference dose and β is the proportionality constant. Dose proportionality was declared if the calculated 90% confidence interval (CI) of β lay within the acceptance range [1 + ln(0.5)/ln( r ), 1 + ln(2.0)/ln( r )] (Sun et al, ), where r is the ratio between the highest and lowest doses in the study. In this study, the maximal dose ratio was 12.6, so the acceptance range was 0.726–1.274.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, its potential anti-inflammatory, anti-hyperreactive and antiremodeling effects on allergen-induced effects in mice asthmatic model have been described . Previous pharmacokinetic studies of this compound in rats and beagle dog after intranasal administration (Xu et al 2007(Xu et al , 2008aJiang et al 2010), and in humans using nasal spray of BCQB 45 lg (Sun et al 2012) demonstrated a long elimination half-life (11.7 ± 7.1 h) but without subchronic toxicity after a long-term toxicokinetics study of intranasal administration of BCQB in dogs ). Also, further study of BCQB in human showed its safety and tolerability after single-dose escalation and multipledose escalation (Sun et al 2012).…”
Section: Introductionmentioning
confidence: 94%
“…Previous pharmacokinetic studies of this compound in rats and beagle dog after intranasal administration (Xu et al 2007(Xu et al , 2008aJiang et al 2010), and in humans using nasal spray of BCQB 45 lg (Sun et al 2012) demonstrated a long elimination half-life (11.7 ± 7.1 h) but without subchronic toxicity after a long-term toxicokinetics study of intranasal administration of BCQB in dogs ). Also, further study of BCQB in human showed its safety and tolerability after single-dose escalation and multipledose escalation (Sun et al 2012). Cytochrome P450 enzymes are mostly involved in the metabolism and disposition of more than 60 % of currently marketed drugs and are considered central in many clinically important drug interactions (Bailey et al 1998;Lim et al 2008;Liu et al 2010).…”
Section: Introductionmentioning
confidence: 94%